The specific Pavlovian-to-instrumental transfer (PIT) effect in humans - Alarcón, Daniel (2016)
In Pavlovian conditioning subjects learn the predictive relation between a conditioned stimulus (CS) and a motivationally significant unconditioned stimulus (US), while in instrumental conditioning subjects learn the predictive relation between their responses and a motivationally significant outcome. Both types of associative learning interact in the phenomenon known as the Pavlovian-to-instrumental transfer (PIT) effect. In a PIT procedure subjects received Pavlovian conditioning, in which different CSs are paired with different outcomes (CS1->O1; CS2->O2, etc), and instrumental training, in which each of different responses are paired with these outcomes (R1->O1; R2->O2, etc). After this training the CSs are presented while subjects have the opportunity to perform the instrumental responses. Studies have found that the CS presentations affect instrumental performance by elevating the rate of responding, and this effect can take two different forms: general and specific. In general PIT, Pavlovian cues elevate performance of any instrumental responses that have been trained with a reinforcer of a similar motivational valence to the US. But in the specific PIT effect a CS paired with a particular outcome selectively elevates instrumental responses that produce that outcome, compared to its effect on responses producing different outcomes, i.e. CS1: R1>R2; CS2: R2>R1. Different mechanisms have been proposed to explain the specific form of the PIT effect but none of these accounts can explain all the evidence that has been found. Some of these mechanisms propose that at test a CS evokes a representation of the outcome that, in turn, elicits those responses trained with that outcome. In contrast, other accounts suggest that the CS elicits responding via a direct association formed during training. The experiments reported in this thesis were conducted to provide further evidence on this phenomenon in order to distinguish between these mechanisms. The experiments presented here used a standard PIT task with humans as participants. In the Pavlovian phase participants received presentations of different neutral fractal images (CSs), which were paired with presentations of drink and food images (outcomes). In the instrumental phase participants had to press two keys on a computer keyboard (instrumental responses), which were reinforced with the outcomes. The specific PIT effect was measured in a test in which participants could perform both instrumental responses in the presence and absence of the Pavlovian cues. The experiments reported in Chapter 2 and 3 made use of a procedure known as conditioned inhibition, in which a conditioned inhibitor (CI) is trained to signal the absence of an expected outcome; it has been proposed that presentations of a CI suppress the activation of an outcome representation. In the experiments presented in Chapter 2 two CIs were established, one for each of the outcomes, while in those reported in Chapter 3 only one CI was trained. In the studies of both chapters the effect of the CIs, both alone and in compound with excitatory CSs, on the specific PIT effect was assessed. The findings revealed that the CIs did not exert any measurable effect when they were presented alone, but they reduced the specific PIT effect produced by the excitatory CSs. In Chapter 4 CSs were trained in either a forward or backward relation with the outcomes and their effect on instrumental performance was also measured. In some of the experiments the CSs trained in a backward relation with the outcome produced the specific PIT effect, while in others they did not. The contributions of both backward and forward associations were also assessed, and the results suggest that only the forward association supported the specific PIT effect. Overall, the findings suggest that the specific PIT effect is mediated by the activation of an outcome representation, although some assumptions are needed in order to explain the data with extant accounts of PIT.